(Division Example)
 
Line 1: Line 1:
 
== Addition/Subtraction Example ==
 
== Addition/Subtraction Example ==
 
<math>(2 + 3*i) + (23 - 15*i) = (23 + 2) + (3*i - 15*i) = 25 - 12*i</math>
 
<math>(2 + 3*i) + (23 - 15*i) = (23 + 2) + (3*i - 15*i) = 25 - 12*i</math>
 +
  
 
<math>(-3 + \sqrt{-18}) + (7 - \sqrt{-8}) = (-3 + \sqrt{9 \times 2 \times -1}) + (7 - \sqrt{4 \times 2 \times -1}) = (-3 + 3\sqrt{2} \times i) + (7 - 2\sqrt{2} \times i) = 4 + \sqrt{2} \times i</math>
 
<math>(-3 + \sqrt{-18}) + (7 - \sqrt{-8}) = (-3 + \sqrt{9 \times 2 \times -1}) + (7 - \sqrt{4 \times 2 \times -1}) = (-3 + 3\sqrt{2} \times i) + (7 - 2\sqrt{2} \times i) = 4 + \sqrt{2} \times i</math>
  
== Division Example ==
+
== Division/Multiplication Example ==
 
<math>\frac{4}{2+3*i}</math> = <math>\frac{4}{2+3*i}\times\frac{2-3*i}{2-3*i}</math> = <math>\frac{8-12*i}{4+6*i-6*i-9i^2}</math> = <math>\frac{8}{13} - \frac{12}{13}\times i</math>
 
<math>\frac{4}{2+3*i}</math> = <math>\frac{4}{2+3*i}\times\frac{2-3*i}{2-3*i}</math> = <math>\frac{8-12*i}{4+6*i-6*i-9i^2}</math> = <math>\frac{8}{13} - \frac{12}{13}\times i</math>
 +
 +
 +
<math>7*i \times (7 - 3*i) = 49*i - 21*i^2 = 49*i - 21*(-1) = 21 + 49*i</math>
 +
 +
== Conjugate Example ==
 +
<math>3 + 5*i  =  3 - 5*i</math>
 +
 +
<math>5 - 20*i  =  5 + 20*i</math>

Latest revision as of 05:47, 3 September 2008

Addition/Subtraction Example

$ (2 + 3*i) + (23 - 15*i) = (23 + 2) + (3*i - 15*i) = 25 - 12*i $


$ (-3 + \sqrt{-18}) + (7 - \sqrt{-8}) = (-3 + \sqrt{9 \times 2 \times -1}) + (7 - \sqrt{4 \times 2 \times -1}) = (-3 + 3\sqrt{2} \times i) + (7 - 2\sqrt{2} \times i) = 4 + \sqrt{2} \times i $

Division/Multiplication Example

$ \frac{4}{2+3*i} $ = $ \frac{4}{2+3*i}\times\frac{2-3*i}{2-3*i} $ = $ \frac{8-12*i}{4+6*i-6*i-9i^2} $ = $ \frac{8}{13} - \frac{12}{13}\times i $


$ 7*i \times (7 - 3*i) = 49*i - 21*i^2 = 49*i - 21*(-1) = 21 + 49*i $

Conjugate Example

$ 3 + 5*i = 3 - 5*i $

$ 5 - 20*i = 5 + 20*i $

Alumni Liaison

Questions/answers with a recent ECE grad

Ryne Rayburn